2014
DOI: 10.1038/ncomms4711
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic competition between spin-density wave order and superconductivity in underdoped Ba1−xKxFe2As2

Abstract: An intriguing aspect of unconventional superconductivity is that it always appears in the vicinity of other competing phases, whose suppression brings the full emergence of superconductivity. In the iron pnictides, these competing phases are marked by a tetragonalto-orthorhombic structural transition and a collinear spin-density wave (SDW) transition. There has been macroscopic evidence for competition between these phases and superconductivity as the magnitude of both the orthorhombicity and magnetic moment a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
9
38
0
Order By: Relevance
“…Thus, to properly disentangle these three contributions ϕ 1 = ϕ Γ , ϕ 3 , and λ we argue that it is necessary to measure simultaneously the splitting of the two doublets at the M point and of the doublet at the Γ point. The interplay between these three parameters may also explain why the doublet splittings are different at these two high-symmetry points, as observed experimentally 16 .…”
Section: Comparison To First-principle Calculations and Arpes Exsupporting
confidence: 51%
See 2 more Smart Citations
“…Thus, to properly disentangle these three contributions ϕ 1 = ϕ Γ , ϕ 3 , and λ we argue that it is necessary to measure simultaneously the splitting of the two doublets at the M point and of the doublet at the Γ point. The interplay between these three parameters may also explain why the doublet splittings are different at these two high-symmetry points, as observed experimentally 16 .…”
Section: Comparison To First-principle Calculations and Arpes Exsupporting
confidence: 51%
“…However, the close proximity of the different electronic energy scales, together with the multi-orbital character of the band structure, render this task non-trivial 13 . For instance, in several iron pnictides, a partial energy gap of about 50 meV reported in optics experiments, and also observed by ARPES at the points where folded and unfolded bands cross, has been attributed to the formation of the metallic SDW order [14][15][16] . This is of the same order of magnitude as the energy splitting attributed to the tetragonal symmetry-breaking arising from the formation of the orthorhombic/nematic phase 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is now well established that a narrow region of phase space exists in the electron-and hole-doped members of these materials in which superconductivity and magnetism strongly compete just before the system crosses into a purely superconducting state upon further doping. [5,6,7,8,9] An in-plane magnetic spin density wave phase produced by Fermi surface nesting is found to lose strength upon doping, with the Néel transition temperature, T N , getting progressively suppressed into a superconducting state which persists and reaches a maximum T c with further doping. [10,11,12] In recent work, we demonstrated that the competition between magnetism and superconductivity is even more surprising and complex than previously thought with the discovery of a new tetragonal magnetic ground state known as the C 4 phase in yet another narrow compositional region within the established phase coexistence pocket.…”
Section: Introductionmentioning
confidence: 99%
“…For weakly/moderately doped FeSCs the common belief is that s +− superconductivity is robust. In this communication we argue that an exotic state which breaks TRS can emerge already at low doping, in a range where SC is known [22][23][24][25][26][27][28][29][30] to emerge from a pre-existing SDW state. Previous works on SC in the coexistence region focused on the SDW-induced modification of the form of s +− gap [31][32][33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%